Trends in hydraulic actuators and components in legged and tough robots: a review. (3rd May 2018) - Suzumori, Koichi; Faudzi, Ahmad Athif
Abstract: Hydraulics is an old technology which is being applied in many applications including large machinery, heavy industries, and early robotics. The traditional features of hydraulics that possess a high power to weight ratio compared to other power transmission system make it suitable to work in a tough and robust environment. However, the trend of hydraulic system has decreased since the introduction and mass usage of the powerful brushless motor and rare earth magnetic motor in industrial sector since the 1980s. Recently, hydraulic systems have shown incremental demand where the innovation of hydraulic actuators and components was actively conducted aimed at compactness, lightweight with higher energy-efficiency, clean and friendly features for many applications in both mobile and industrial hydraulics. This review shows the hydraulic trends in tough robotics applications which focus on legged robots such as humanoid, search and rescue robot and large machinery. New innovations of hydraulic components such as actuators, pump, and other accessories and trends are discussed for future hydraulics in tough robotics applications. Abstract :